Geotagging of natural history collections for reuse in environmental research - Maciej M. Nowak (Elsevier, 2021)
The availability of archival spatial datasets, which are crucial means of obtaining valuable information in biological and ecological research, is often limited due to the analog form of the data. Therefore, digitization projects of natural history collections (NHCs) currently show a rising trend. Increasingly, these projects include geotagging, which means assigning geographical coordinates and spatial attributes to specimens discovered in the field. Although numerous studies have examined the process of digitizing NHCs, there is still a need to develop good practice guides and a unified database or list of geographical information resources. Moreover, the accuracy of the spatial assignment of specimen locations in many online databases is unacceptable for environmental research. Therefore, it is important to develop a methodology to standardize geotagging methods.The first goal of this paper was to create and verify a list of available online sources of geotagged spatial information. The second goal was to develop a good practice guide for geotagging NHCs based on the limitations resulting from the specificity of archival data. These aims were achieved owing to participation in the AMU Nature Collections project – digitization and sharing of natural data resources of the Faculty of Biology of Adam Mickiewicz University in Poznań (AMUNATCOLL). The results of the proposed methodology indicate that natural history data are so heterogeneous in terms of spatial description quality that it is not always possible to unambiguously and precisely geotag them. Therefore, it is important to implement the spatial quality assessment and commenting system proposed by the authors.